Asymmetric Regional Development as a Framework for Achieving Spatial and Regional Justice in Indonesia - Indra, Mexsasai; Saragih, Geofani Milthree; Ismandianto, Ismandianto; Muthia, Arini Azka (Jambura Law Review, 2026)
Indonesia continues to experience persistent territorial disparities as a result of the long-standing application of symmetric decentralization, under which uniform administrative standards are imposed on regions with fundamentally different structural capacities. This approach has contributed to chronic governance underperformance and spatial injustice. The resulting mismatch between regional heterogeneity and policy uniformity underscores the need for a conceptual reorientation grounded in normative theories of justice and constitutional principles. This article aims to develop a coherent framework for asymmetric regional development capable of addressing structural inequalities while remaining consistent with the constitutional architecture of the Unitary State. Using a normative legal research approach that combines statutory analysis with case studies of Aceh, Papua, and Yogyakarta, this study investigates how asymmetric arrangements can be operationalized as both legally legitimate and philosophically justified governance models.The article presents four key contributions: first, it reconceptualizes asymmetric regional development as an ethical and constitutional imperative, grounded in Rawlsian distributive justice, Sen’s capability approach, and contemporary spatial justice theory; second, it highlights the policy pitfalls of symmetric decentralization through a critical assessment of historical and empirical evidence, including failures in regions such as Malaka; third, it introduces the Regional Inclusion Feasibility Index (IKPD) as a juridical and technocratic innovation, providing objective, multidimensional criteria for regional expansion; and fourth, it situates Indonesia’s asymmetric model within global comparative practices, demonstrating its alignment with principles of proportional autonomy and contextual justice. Collectively, these contributions position asymmetric regional development as a viable pathway toward equitable and sustainable territorial governance in Indonesia.